Lexical and Morphological Means of Colour Names Formation in Arabic - Zarytovskaya, V.N. (Vestnik Rossijskogo universiteta družby narodov. Seriâ: Teoriâ âzyka, semiotika, semantika (Online), 2017)
The article is devoted to the semantic field of colours in Arabic language and the peculiarities of its composition in comparison with the Russian. For the first time the author explores the means (borrowing and metaphorization) and methods of formation (special grammar patterns) of the Arabic colour names (rather then base tints) and makes this on extensive language material. The study addresses the actual issues of cultural character: the reflection of the world picture in the language as a quantitative representation of shades of a particular colour, and character of objects wich participated in the secondary nominations of colour. The results of the study allow to conclude about the complexity of the semantic field of colours in Arabic, the great potential of its derivational possibilities and systematic intersections with fields of different semantics.